Geneva's “Enlightened Orthodoxy”: The Middle Way of Jacob Vernet (1698–1789) - Sorkin, David (Church history, 2005)
Jacob Vernet (1698–1789) numbers among those eighteenth-century theologians whose relationships to the philosophes have saved them from being forgotten but at the cost of being misrepresented. Vernet is usually remembered for editing the first edition of Montesquieu's De l'esprit des lois, helping to restore Rousseau to Calvinism, and corresponding and then crossing swords with D'Alembert and Voltaire: it is especially the controversy with D'Alembert surrounding the article on “Geneva” in the seventh volume of the Encyclopédie (1757), as well as a sustained conflict with Voltaire over many issues, that have secured him scholarly attention. The scholars who have noticed Vernet have accordingly concentrated on aspects of his person: ascertaining whether he was mendacious, conniving, and hypocritical, as some of the philosophes, especially Voltaire contended, or the figure of impeccable behavior and conscience suggested by his office and his hagiographers. This one-sided emphasis on his person obscures the fact that Vernet wrote a shelf of books and was such an influential figure that he was the representative Genevan theologian of his day. The neglect of his thought is hardly astounding, however, since it is characteristic of the treatment accorded eighteenth-century theology in general. Theologians and students of religion have for long dismissed eighteenth-century theology as derivative; students of the Enlightenment have considered it outside the canon of Enlightenment literature and thus beyond their purview. Both these assumptions should be challenged.